Islam Moderat sebagai Penangkal Radikalisme - Mahmudi Mahmudi (Proceedings of Annual Conference for Muslim Scholars, 2018)
The radicalization of religion is a religious problem that needs to be solved. If there is no solution, religious radicalization will lead to our national divisions. Thus, it is necessary to examine the Abdurrahman Wahid and Quraish Shihab’s thought. Both figures offering a flexible, soft, and far from violent and radical Islam. The method of writing in this article is descriptive and explorative method. This paper found the conclusion that the moderate Islamic thought of Abdurrahman Wahid and Quraish Shihab is characterized by Tolerance, Compassion, plurality of interpretation and spirituality. The moderate Islamic thought of these two figures can be a deterrent to the current flow of radicalism.